BIOLOGY AND FISHERY OF WAM MURAENESOX TALABONOIDES (SLEEKER) - George, M K (Indian Journal of Fisheries, 2011)
Medium sized Warn, Muraenesox talabonoides (Bleeker) belonging to110.5-130.5 cm size groups dominated the offshore catch, while size groups, smallerand larger than these mainly contributed to the inshore catch due probably iogear selection. Small sciaenids (dhoma) appear to be the favoured food ite.n ofoffshore warn. High incidence of empty stomachs was recorded in offshore warn.Significant deviation of sex ratio occured in wam larger than 135 cm. The lengthat first maturity in female is 120 cm and in male 105 cm. Fecundity varied inspecimens of different length and significantly in specimens of the same length.'Peak of spawning appears to be in May, foUowjd by a possible secondary spawningaround September. Spawning ground of warn may extend from Bombay toiKutch. Wam landings formed an average 7.5 per cent of the trawler catch. Catchand catch rate were thÂ« highest in the third quarter of all the years.